Infection of Infectious Spleen and Kidney Necrosis Virus and Viral Nervouse Necrosis in Seawater Fish Identifed Using Multiplex Polymerase Chain Reaction - Hidayati Kumalasari; Putu Eka Sudaryatma; Artanti Tri Lestari; Wahyu Nurlita; Wahyu Andy Nugraha; Nur Hasanah; Ida Ayu Mirah Meliana Dewi; Ni Putu Arya Shintya Anggraeni (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
Indonesia become a maritime country with large of ocean area and beach line with marine species diversity reaches 37% of the world’s fish. This makes Indonesia have aquaculture potential that supported by an appropriate climate. However, the challenge of viral diseases caused by Infectious Spleen and Kidney Necrosis Virus (ISKNV) and Viral Nervous Necrosis (VNN) would hamper marine aquaculture and causing huge economic losses. Therefore, it is necessary to carry out early detection methods that are efficient, fast, precise and accurate to identifying these viral disease. Here we developed a multiplex-PCR (mPCR) a method that can detect simultaneously of the ISKNV and VNN. The results of this method showed high sensitivity and specificity by using MCP and CP gene target primers to detect ISKNV and VNN, respectively. From a total of 353 samples of seawater fish examined by mPCR, positive results following of single infection of ISKNV and VNN were 14 and 2, respectively. We also found that 18 grouper fish was co-infection with these viruses. From these results, it shows that the mPCR method developed has efficiency, faster and high accuracy. This founding was possible to be applied in laboratory testing or early detection system in the field for ISKNV and VNN.